Governing marine cloud brightening for ecosystem conservation under a warming climate - Rose Foster; Nicole Shumway; Daniel Harrison; Pedro Fidelman (Earth System Governance)
Marine Cloud Brightening (MCB) is an emerging technology designed to mitigate the impacts of climate change by increasing the reflectivity of low-lying marine clouds. As research into this technology advances, the question of how to govern its trials and deployment becomes increasingly important. This paper identifies 12 challenges and 13 recommendations for governance of MCB, based on a systematic review of 27 publications. These findings are explored in relation to the design of effective MCB governance, with a particular focus on potential small-scale applications for ecosystem conservation purposes, like coral bleaching mitigation. The paper underscores the existing knowledge gaps and potential avenues for future MCB governance research, contributing to the burgeoning literature on the governance of innovative technologies aimed at addressing global environmental challenges. To manage potential risks and maximise potential benefits, it is crucial to understand the governance challenges MCB presents and explore options to address these challenges.